Analisa Kepuasan Masyarakat Terhadap Pelayanan di Kantor Kelurahan Jatiwaringin Kota Bekasi Menggunakan Metode Servqual - nabila mumtazah; saghifa Fitriana (Informatics and Computer Engineering Journal, 2021)
Community satisfaction is one of the indicators of the success of an agency in performing various tasks. With a sense of satisfaction from the community, shows the value to the performance of the agency. This research was conducted to find out the satisfaction of the community to the service in the jatiwaringin village office, it is necessary to conduct an analysis to identify what is needed by the community regarding the services provided by jatiwaringin village. The method used is servqual method consisting of five main dimensions, namely tangible, reliability, responsiveness, assurance, and empathy. So that it can know the level of public satisfaction from various aspects. After the analysis, the result is that the overall gap has a negative value. So that the community is not satisfied with the services provided by the Jatiwaringin Village Office in Bekasi City. The priority of performance that needs to be improved again is on reliability dimension with gap value -0.63 and tangible dimension with gap value -0.59. This proves that community satisfaction affects the quality of service in jatiwaringin village office in Bekasi City. Keywords: Servqual Method, Satisfaction, Service, Jatiwaringin Village